(untitled) - Nguyen, Thi Phuong Hong (Netherlands, 2013)
Although communicative approaches to foreign or second language teaching have proven to be more effective than purely structure-based approaches (Spada & Lightbown 2013), the latter persist, probably because teachers believe that grammar and syntax form the core of language. It is argued in the current paper that this view of language is flawed and should be replaced with a dynamic usage based (DUB) view of language, which holds that language is nothing but a large array of conventionalized expressions, all form-meaning mappings with different levels of specificity or schematicity (Langacker 2000). These are learned as a result of frequent and meaningful exposure to and use of language by both L1 and L2 learners. In other words, all form-meaning mappings at all levels are equally important and need to be focused on in teaching a foreign language. After a theoretical discussion, the chapter briefly reports on a longitudinal experiment in which a communicative approach, based on DUB principles, is tried out in a university classroom in Vietnam. The results are convincing: on several measures of English proficiency, the DUB group scored significantly higher than the group of learners who learned English as a foreign language with a task and structure based approach.
Keywords: Ngôn ngữ và ngôn ngữ khác,Language and languages; Dạy và học,Study and teaching